Dolomitization models in the Sibzar Formation (Middle Devonian), Binalood Mountains (NE Iran): Based on the petrographic and geochemical evidence. (April 2021) - Jamshidipour, Abolfazl; Khanehbad, Mohammad; Moussavi-Harami, Reza; Mahboubi, Asadollah
Abstract: Lithostratigraphically, Sibzar Formation (Middle Devonian) in the Kharv section (Binalood Mountains, NE Iran) with a thickness of 334 m consists of three units (in ascending order): dolostone with intercalations sandstone, middle basaltic sill, and upper dolostone. Three types of dolomite have been identified based on crystal size and shape. Fine crystalline dolomite (D1 ; finer than 30 μm) consist of Nonplanar-a dolomites. Fine to medium crystalline dolomite (D2 ; 20 to 150 μm) consist of mostly Nonplanar-a dolomites and some dolomites are Planar-s and Planar-e. Vein dolomites (Vd; 40 to 700 μm) have a very diverse crystalline texture and are mostly Planar-s, Planar-e and some Nonplanar-a. Cathodoluminescence technique studies also showed that most of these dolomites have dull red luminescence, in some veins with bright red luminescence and zoning. Based on the X-ray diffraction (XRD) and ICP-OES, all dolomites are nearly stoichiometric dolomite and relatively well ordered. Elemental analysis and stable isotope studies show that the concentration of minor elements such as sodium (D1: 822–1365 ppm; D2: 1016–1241 ppm; Vd: 971–1072 ppm), strontium (D1: 257–963 ppm; D2: 134–1334 ppm; Vd: 144–379 ppm), manganese (D1: 560–3675 ppm; D2: 1039–2168 ppm; Vd: 1818–3454 ppm), and iron (D1: 15997-30080 ppm; D2: 8288–18456 ppm; Vd: 19304-25618 ppm) in these dolomites were high and the values of the stable isotope of oxygen (D1: -9.1 to −5.9‰; D2: -7.6 to −6.1‰; Vd: -11.1 to −7.2‰) and carbon (D1: -3.5 to −2.5‰; D2: -5.2 to −1.3‰; Vd: -2 to −1.6‰) were low. The high values of iron and manganese and depletion of the carbon and oxygen isotopes can be related to the effects of high-temperature diagenetic fluids caused by basaltic sill during the burial. These dolomites formed in tidal environment and burial diagenesis in this Formation. Seawater, connate seawaters, saline basinal fluid, and magnesium-rich hypersaline fluids are the main source of magnesium ion (Mg 2+ ) for dolomites of this Formation. Highlights: Three types of dolomite have been identified in Sibzar Formation based on the size and shape. High values of sodium element in these dolomites due to the high evaporation of seawater. Effect of the basaltic sill on the high values of iron and manganese in these dolomites. These dolomites had been formed in the tidal environment and during burial diagenesis. Seawater and hypersaline fluids were sources of most of the Mg 2+ ions in these dolomites.